Unsteady Flow Patterns between Two Egg-Carton Corrugated Plates - GIRÓN-PALOMARES, Benjamin; HERNÁNDEZ-GUERRERO, Abel; ROMERO-MÉNDEZ, Ricardo; HE, Qiang (Engineering Transactions, 2021)
Unsteady analyses of the flow between two egg-carton corrugated plates were performed. Geometry effects on the flow were as follows: “closed recirculations” shrank downstream the channel and became “open recirculations”. For the 180° egg-carton plates, recirculations were z-symmetric to the channel center. Reynolds number increments favored recirculation growth and flow detachment. Transient development effects were as follows: the steady state was reached faster in waves closer to the channel entrance. As time advanced, spatial flow development advanced toward the channel outlet , and y-concave geometries inhibited fluid detachment and steady state achievement. Consequences of the geometry on theransient development of the flow were as follows: the recirculations appeared at larger times, they were smaller, and became “open recirculations” closer to the channel inlet for the 0° model, and the 0° model flow reached a steady state faster. Finally, no clear evidence of unsteady features called “rolling vortices” was observed. Such unsteady features might be a consequence of small unavoidable experimental uncertainties creating a pulsating flow.